Coexpression of exogenous and endogenous mouse mammary tumor virus RNA in vivo results in viral recombination and broadens the virus host range. - Golovkina, T V (1994)
Mouse mammary tumor virus is a replication-competent B-type murine retrovirus responsible for mammary gland tumorigenesis in some strains of laboratory mice. Mouse mammary tumor virus is transmitted horizontally through the milk (exogenous or milk-borne virus) to susceptible offspring or vertically through the germ line (endogenous provirus). Exogenously acquired and some endogenous mouse mammary tumor viruses are expressed at high levels in lactating mammary glands. We show here that there is packaging of the endogenous Mtv-1 virus, which is expressed at high levels in the lactating mammary glands of C3H/HeN mice, by the virions of exogenous C3H mouse mammary tumor virus [MMTV(C3H)]. The mammary tumors induced in C3H/HeN mice infected with exogenous MMTV (C3H) virus contained integrated copies of recombinant virus containing a region of the env gene from an endogenous virus. This finding indicates that there was copackaging of the Mtv-1 and MMTV(C3H) RNAs in the same virions. Moreover, because Mtv-1 encodes a superantigen protein with a V beta specificity different from that encoded by the exogenous virus, the packaging of Mtv-1 results in an infectious virus with a broader host range than MMTV(C3H).